CELF2 suppresses non-small cell lung carcinoma growth by inhibiting the PREX2-PTEN interaction. (25th June 2019) - Yeung, Yiu To; Fan, Suyu; Lu, Bingbing; Yin, Shuying; Yang, Sen; Nie, Wenna; Wang, Meixian; Zhou, Liting; Li, Tiepeng; Li, Xiang; Bode, Ann M; Dong, Zigang
Abstract: The phosphoinositide 3-kinase (PI3-K)/Akt signaling pathway is important in the regulation of cell proliferation through its production of phosphatidylinositol 3, 4, 5-triphosphate (PIP3). Activation of this pathway is frequently observed in human cancers, including non-small cell lung carcinoma. The PI3-K/Akt pathway is negatively regulated by the dual-specificity phosphatase and tensin homolog (PTEN) protein. PTEN acts as a direct antagonist of PI3-K by dephosphorylating PIP3. Studies have shown that PTEN phosphatase activity is inhibited by PREX2, a guanine nucleotide exchanger factor (GEF). Multiple studies revealed that CELF2, an RNA binding protein, cooperates synergistically with PTEN as a tumor suppressor in multiple cancers. However, the underlying mechanism as to how CELF2 enhances PTEN activity remains unclear. Here, we report that CELF2 interacts with PREX2 and reduces the association of PREX2 with PTEN. Consistent with this observation, PTEN phosphatase activity is upregulated with CELF2 overexpression. In addition, overexpression of CELF2 represses both Akt phosphorylation and cell proliferation only in the presence of PTEN. In an ex vivo study, CELF2 gene delivery could significantly inhibit patient-derived xenografts (PDX) tumor growth. To further investigate the clinical relevance of this finding, we analyzed 87 paired clinical lung adenocarcinoma samples and the results showed that CELF2 protein expression is downregulated in tumor tissues and associated with poor prognosis. The CELF2 gene is located on the chromosome 10p arm, a region frequently lost in human cancers, including breast invasive carcinoma, low-grade glioma and glioblastoma. Analysis of TCGA datasets showed that CELF2 expression is also associated with shorter patient survival time in all these cancers. Overall, our work suggests that CELF2 plays a novel role in PI3-K signaling by antagonizing the oncogenic effect of PREX2. Abstract : CELF2 plays a key role in PI3-K signaling by antagonizing the oncogenic effect of PREX2 and inhibits non-small cell lung cancer growth.